Recent Eco-Friendly Developments in Personal Protective Clothing Materials for Reducing Plastic Pollution: A Review - Memon, A. H.; Peerzada, M. H.; Muhammad, K.; Memon, S. A.; Mangi, S. A.; Mujtaba, G. (Engineering, Technology & Applied Science Research, 2019)
Due to the industrialization increase in the 20th century, the level of hazards for public health and the demand for personnel protective clothing (PPC) have increased. The area of PPC has been steered to high tech equipment made from plastic-based materials, which are derived from non-renewable sources and have a long life cycle expanding from hundreds to thousands of years, after their end of useful life. This paper reviews the information related to conventional plastic-based fibers, their properties, advantages, disadvantages, and applications in the battlefield, industry, automobiles, etc. This paper provides a basis for the selection of natural fibers and the replacement of conventional plastic-based fibers to reduce the plastic content in protective clothing or other composites. A comparative analysis of technological, environmental, economic and legal aspects of plastic-based and environment-friendly natural fibers is presented. Natural fiber-based composite protective clothing is found to be environment-friendly and considered to have prospects for the future due to its comparative technological, environmental, economic and legal advantages.